Heart Development and Disease - Dubois, Nicole (Nicole C.) (Current topics in developmental biology, 2024)
Heart Development and Disease, Volume 156 in the Current Topics in Developmental Biology series, highlights new advances in the field, with this new volume presenting interesting chapters including Macrophages during heart valve development, Computational models of cardiovascular biology, Mechanisms of early sarcomere assembly, Role of RNA binding proteins during heart development and disease, Early heart development and morphogenesis, PSC models for development and disease, ECM or SHF development, Role of metabolism during heart development, Cellular ploidy in cardiac biology, and Genetics of CHD in the human population.